Bagaimana Trichoderma Meningkatkan Enzim Pertahanan pada Tanaman Pangan: Pandangan Saat Ini dan Perspektif Masa Depan di Asia - Albana, Hasan; Nurbailis, Nurbailis; Darnetty, Darnetty (Universitas Andalas, 2024)
Food crops are plants grown for consumption by humans and animals. These crops face threats from both abiotic and biotic factors. Therefore, environmentally friendly alternative controls are needed, such as enhancing plant resistance using Trichoderma spp. This systematic literature review provides information on the effects of Trichoderma spp. application on plant physiology, particularly focusing on defense enzymes in food crops in the Asian region. Articles on the effects of Trichoderma application on food crop defense enzymes in Asia were retrieved from PubMed and Scopus. The literature search yielded 3,022 articles from these databases. Four criteria were established for study inclusion: i) studies involving Trichoderma spp.; ii) studies using food crops as the subject; iii) studies conducted in Asia; and iv) studies evaluating at least one defense enzyme activity. India has conducted the most research on this topic, with a total of 26 studies. Across 43 reviewed articles, 100 isolates were identified. The most frequently used Trichoderma species was T. harzianum, and the most common inoculation method was seed treatment, reported in 25 articles. Additionally, 50% of the articles conducted their studies in controlled environments. Trichoderma spp., known for enhancing plant resistance, also have the ability to increase certain physiological aspects of plants, such as defense enzyme activity. More research on changes in plant enzymes due to Trichoderma application is recommended, especially in field conditions, to assess its effectiveness in practical, real-world settings.